Ichthyological Investigations in River Chaliyar, Kerala - M.B., Raghunathan (Fishery Technology, 2025)
41 species of fish belonging to 27 genera were recorded during icthyological investigaiipns in River Chaliyar, Kerala, India during 1984-87. Preliminary information on species divetsitv in estuarine, plains and mountainous courses; and premonsoon, monsoon and postmonsoohjjeriods are provided.